Effect of different catching practices during manual upright handling on broiler welfare and behavior - De Lima, Victor Abreu [UNESP]; Ceballos, Maria Camila; Gregory, Neville G.; Da Costa, Mateus J. R. Paranhos [UNESP] (Elsevier, 2019)
The aim of this study was to identify the influence of different catching practices during manual upright handling on broiler welfare and behavior. Catching was examined in a total of 4,595 Cobb broilers with average live weight of 3.2 kg and 42 days old. Six catching practices were evaluated: shed curtain position, loading time, catching method, catching team, height of the crates from the floor, and placement of the bird in the crate. Behavioral welfare indicators were defined as follows: 1) broiler agitation in the catcher's hands, measured when the birds flapped their wings, kicked, or wriggled in the hands; 2) broiler striking the crate entrance as it was being placed in the crate, measured when the birds get the head, wings, or legs, hit at the crate entrance; and 3) broiler agitation in the crate, measured when birds flapped the wings or jumped inside the crate for 3 s or more after placement in the crate. A logistic regression model was used to calculate the chance of occurrence of each behavioral welfare indicator due to the handling factors. All catching practices evaluated in the present study influenced the birds' welfare and behavior. Thus, some procedures during broiler catching potentially improved their behavior, making them less prone to accidents, and consequently improved their welfare. The catching process should be performed with the curtains in the closed position, carrying one broiler per catcher in an upright position while containing its wings, carefully placing the birds inside the crates, and with the crates being positioned at a height of at least 21 cm from the ground. Additionally, it was concluded that more attention should be given to the broiler catchers, since the position of the curtain, loading time, and position of the crate during handling can influence the work done by them, affecting the welfare and behavior of both humans and birds.
Keywords: human-animal relationship; poultry; pre-slaughter handling; stockperson